Corruption - no rule of law - no democracy: could separately elected Attorneys General in a divided executive give Africa new hope? Experiences from the U. States of A - Teshome, Tilahun (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2008.